Pola Pergeseran Strategi Nafkah Masyarakat Desa (Studi Kasus Petani di Desa Sindangsari Kec, Pabuaran Serang Banten) - Agustin, Nurmalasari; Hayat, Nurul; Afrizal, Stevany (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This research constructs a shift in livelihood strategies in the Sindangsari Village community from the agricultural sector to the non-agricultural sector. The livelihood strategy adopted by the people of Sindangsari Village is generally to become farmers who own land and farm laborers. This research is also aimed at analyzing the economic welfare of farmers after making the shift and what livelihood strategies are being implemented now. The area was determined deliberately, namely (purposively) in the Pabuaran sub-district, Serang district. This research uses a qualitative research method with an ethnographic approach. The data is obtained through interviews, observations and literature studies so that findings can be found which are expected to be used to develop knowledge regarding the changing livelihood strategies of the Pabuaran sub-district community. The results of this research reveal that a shift in livelihood strategies occurred in the Sindangsri village farming community due to inappropriate economic factors, minimal wage income, agricultural problems and a shift in the function of agricultural land. so that many people are making the shift, especially farmers. So it requires the people of Sindangsrai Village to implement a livelihood strategy by trading and opening other businesses. This research is linked to the farmer's moral economic theory (Jamesscotes safy firs) self-preservation theory.